The Effect Of Company Size, Leverage Profitability, Liquidity, And Efficiency On Financial Distress - Muhammad Rizqi Darmawan; Triyono (Paradoks : Jurnal Ilmu Ekonomi, 2025)
The purpose of this study is to analyze the effect of company size, leverage, profitability, liquidity, and efficiency on financial distress (an empirical study of property and real estate companies listed on the IDX in 2021-2024). This study uses a quantitative method. The type of data used in this study is secondary data. The data source comes from the official IDX website. The data collection techniques used in this study include literature review and documentary analysis. The data analysis techniques employed in this study include hypothesis testing, multiple regression analysis, coefficient of determination testing, F-test, t-test, classical assumption testing, normality testing, multicollinearity testing, autocorrelation testing, and heteroskedasticity testing. The results of this study indicate that company size does not have a significant effect on financial distress. Leverage has a significant effect on financial distress. Profitability has a significant effect on financial distress. Liquidity does not have a significant effect on financial distress. Efficiency does not have a significant effect on financial distress.